The perception of emerging cattle farmers on extension and advisory services in improving the welfare of their cattle in Sinthumule-Kutama Areas of Makhado Municipality in Vhembe District, in Limpopo Province - Thononda, Muano (My University, 2023)
The study was carried to find out the perceptions that emerging cattle farmers hold regarding the importance of agricultural extension, the role and the impact of extension advisors in improving the welfare of their cattle in Sinthumule-Kutama areas. Primary data was collected from emerging cattle farmers of Sinthumule-Kutama areas, under Makhado municipality using questionnaires. The target population was emerging cattle farmers of Sinthumule-Kutama areas. Simple random sampling method was used to select sixty seven (67) emerging cattle farmers from the targeted areas (18 villages) but extra 13 farmers were interviewed and the total of interviewed farmers is 80. SPSS tool was used for descriptive analysis (percentage) and the mean score to address the objectives of the study. Majority of emerging cattle farmers were found to be older than 50 years and majority of these farmers are female. Majority of farmers had primary education as their highest qualification, however male farmers were found to be more educated than female farmers. Many of them are married, pensioners and they rely on non-farming activities for source of income. Seven statements were used to measure perceptions of farmers towards AEAS, farmers agreed with four statements regarding their perception towards AEAS in helping them with improving their cattle welfare. Farmers agreed on statements like cattle welfare is important in farming, AEAS are important in cattle farming, they are knowledgeable about cattle welfare and methods used by extension workers are important. This shows that emerging cattle farmers of Sinthumule-Kutama regard agricultural advisors as important bodies in their cattle welfare improvement. Results further indicated that majority of farmers are receiving services and advice from extension workers on their cattle welfare. Majority of farmers further revealed that the extension activities contribute to their knowledge of cattle welfare and that they receive the support regarding their cattle welfare from extension workers, for instance; extension workers arrange animal technicians to inject their livestock and provide medications after every season in areas and places without animal handling facilities such as crush pen. Extension workers collaborate with some of these farmer who are leaders within the community to manage cattle welfare when extension worker is not around .The results further revealed that majority of farmers rely on those leaders as they are accessible ,they expect them to perform extension work and to vaccinate cattle during animal health emergence. Majority, here refers to half of the respondents of farmers stated that the activities held by extension workers are meetings, furthermore emerging cattle farmers of Sinthumule-Kutama are expecting to be getting medication every time not only when season changes and they are also expecting to be trained, they believe that these expected services can help them improve their cattle welfare.
Thesis (M.A. Agricultural Management (Agricultural Extension)) -- University of Limpopo, 2023
Keywords: Agricultural extension and advisory services; Cattle welfare; Emerging cattle farmers; Perception; Agricultural extension work; Livestock farms; Cattle